Institutional Economics: Perspectives and Methods in Pursuit of a Better World - Whalen, Charles J. (Routledge, 2021)
Institutional economics is a sociocultural discipline and policy science which draws on the idea that economies are best understood through an appreciation of history, real-world institutions, and socioeconomic interrelations. This book brings together leading institutionalists to examine the tradition’s most essential perspectives and methods. The contributors to the book draw on a broad range of institutional thought from the classic work of Thorstein Veblen, John R. Commons, and Karl Polanyi, to the newer viewpoints of post-Keynesian institutionalism, feminist institutionalism, and environmental institutionalism. Methods range from frameworks used to analyze public policy and institutional change, to modes of analysis including myth busting, historically grounded narratives, and computer-based simulations. Each chapter surveys the origins, development, key features, applications, and frontiers of a particular viewpoint, framework, or mode of analysis. Due consideration is given to both strengths and weaknesses; and woven into the chapters is attention to core institutionalist concepts, including technology, institutions, culture, and complexity. The book provides economists with promising starting points for new research, students with contributions refreshingly in touch with the real world, and policymakers and social scientists with compelling reasons for engaging further with the institutionalist tradition.
Keywords: economic history; economic theory; institutional economics

Constituting the Political Economy of the Kurds: Social Embeddedness, Hegemony, and Identity - Tekdemir, Omer (Routledge, 2021)
This book examines the development of Kurdish political economy and the emergence of collective Kurdish identity within a historical context through three main periods: the late-Ottoman Empire, the initial Republican Turkey era, and then the post-1990s period. It relates historical developments to the dynamics of Kurdish society, including the anthropological realities of the nineteenth century through the moral economy frame, the evolving nature of nationalism in the early twentieth century and the more recent construction of a modern political Kurdishness by means of radical democracy, and an agonistic pluralism shaped by left-wing populism.
Keywords: Kurdistan; Political Science / World / Middle Eastern; embeddedness; ethnic studies; middle eastern studies; regional studies